A role for AT1 receptor-associated proteins in blood pressure regulation. (April 2015) - Castrop, Hayo
Highlights: Several accessory proteins interact with AT1 and AT2 receptors. Atrap supports the internalization of the AT1 receptor. Arap1 facilitates the surface expression of the AT1 receptor. Abstract : The renin angiotensin-system is one of the most important humoral regulators of blood pressure. The recently discovered angiotensin receptor-associated proteins serve as local modulators of the renin angiotensin-system. These proteins interact with the AT1 receptor in a tissue-specific manner and regulate the sensitivity of the target cell for angiotensin II. The predominant effect of the AT1 receptor-associated proteins on angiotensin II-induced signaling is the modulation of the surface expression of the AT1 receptor. This review provides an overview of our current knowledge with respect to the relevance of AT1 receptor-associated proteins for blood pressure regulation. Two aspects of blood pressure regulation will be discussed in detail: angiotensin II-dependent volume homoeostasis and vascular resistance.